Pengaruh Teknologi Pembelajaran Dan Dukungan Sosial Terhadap Kinerja Guru Sekolah Dasar di Kecamatan Muara Sugihan - Desi Anjas Sasmita; Syaiful Eddy; Suherman Suherman (CV. Ulil Albab Corp, 2026)
This study aims to determine and analyze: (1) the influence of learning technology on teacher performance; (2) the influence of social support on teacher performance; and (3) the simultaneous influence of learning technology and social support on teacher performance. This research is a quantitative study using a multiple correlation method. The study was conducted at public elementary schools in Muara Sugihan District, with 92 teachers as respondents. Data were collected through questionnaires, observations, and documentation. The validity test used construct validity, while the reliability test employed Cronbach’s Alpha. The prerequisite tests included normality, homogeneity, and linearity tests. The data were analyzed using simple and multiple linear regression techniques. The results showed that learning technology and social support have both partial and simultaneous influences on teacher performance in public elementary schools in Muara Sugihan District. The contribution of learning technology and social support variables to teacher performance was 28.2%, while the remaining 71.8% was influenced by other variables not examined in this study.